2001
DOI: 10.1007/s004280100475
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in poorly differentiated endocrine colon carcinomas developing in tubulo-villous adenomas: a report of two cases

Abstract: The genetic study of two cases of tubulovillous adenoma associated with poorly differentiated endocrine carcinoma (PDEC) is reported. Aim of this work was to assess whether the exocrine and endocrine growths share a common genotype. The analysis entailed the search for allelic loss (LOH) or imbalances of polymorphic microsatellite markers at the corresponding chromosomal loci of the genes MEN-1 (11q13), p53 (17p13). Deleted in Colorectal Carcinoma (DCC) (18q21) and hMSH-2 (BAT26) (2p21-22). Additionally, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…14,38 Nonetheless, recent reports of frequent 18q LOH in midgut carcinoids indicate that a novel putative tumor suppressor gene (distinct from DCC or DPC4) that is located on 18q may play an important role in the pathogenesis of midgut endocrine tumors. 15,16 In an attempt to evaluate whether the pathogenesis of PDECs is more consistent with that of WDECs, as suggested by some studies, [5][6][7][8] or with that of classical nonendocrine adenocarcinomas (i.e., CRCs), as suggested by other reports, 3,4 we compared the gastric subset of PDECs with a series of gastric WDECs and also compared the colorectal subset of PDECs with a series of CRCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,38 Nonetheless, recent reports of frequent 18q LOH in midgut carcinoids indicate that a novel putative tumor suppressor gene (distinct from DCC or DPC4) that is located on 18q may play an important role in the pathogenesis of midgut endocrine tumors. 15,16 In an attempt to evaluate whether the pathogenesis of PDECs is more consistent with that of WDECs, as suggested by some studies, [5][6][7][8] or with that of classical nonendocrine adenocarcinomas (i.e., CRCs), as suggested by other reports, 3,4 we compared the gastric subset of PDECs with a series of gastric WDECs and also compared the colorectal subset of PDECs with a series of CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In contrast, another study, on mixed glandular-neuroendocrine carcinomas, found different genetic alterations in the two tumor components. 5 Furthermore, some studies on gastric PDECs have revealed extensive allelic deletions in the region containing the MEN1 gene that are responsible for multiple endocrine neoplasia type 1 syndrome. This finding is similar to what has been observed in the corresponding well-differentiated tumors and suggests a mechanism of pathogenesis that involves the dedifferentiation of previously differentiated endocrine neoplasms.…”
mentioning
confidence: 99%
“…It has been suggested that NECs either originate from multipotent stem cells, which also may be the origin of nonneuroendocrine adenocarcinomas, or arise from the dedifferentiation of well differentiated NENs. [30][31][32][33][34][35] The latter possibility is less likely, because it is rare to identify tumors that have separate components of well differentiated NET and poorly differentiated NEC.…”
Section: Diagnosis and Classificationmentioning
confidence: 99%
“…Some have argued, based on the association of neuroendocrine carcinomas/neoplasms to adenomas, adenocarcinomas and even squamous cell carcinoma, that both components of a mixed neoplasm are derived from a single transformed pluripotent stem cell, which could otherwise potentially differentiate into mucus, ciliated or endocrine cells [9][10][11][15][16][17] . Recent molecular studies, however, have failed to show shared molecular/genetic pathways including loss of heterozygosity or imbalance of polymorphic microsatellite marker genes such as MEN-1, p53, DCC, and hMSH-2, suggesting significant differences in the pathogenesis and development of the epithelial tumor elements that make up mixed neoplasms [18] .…”
Section: Discussionmentioning
confidence: 99%